Using accelerometry to quantify deceleration during a high-intensity soccer turning manoeuvre - Nedergaard, N. J.; Kersting, U.; Lake, M. (Journal of Sports Sciences, 2014)
The mechanics of cutting movements have been investigated extensively, but few studies have considered the rapid deceleration phase prior to turning which has been linked to muscle damage. This study used accelerometry to examine the influence of turning intensity on the last three steps of a severe turn.